Sperm dilution ratio affects post-thaw motility rate and velocity of Prochilodus lineatus (Characiformes) sperm. Issue 5 (18th December 2015) - Viveiros, Ana T.M.; Leal, Marcelo C.
Summary: There is a lack of standardization in sperm cryopreservation of aquatic organisms and, thus, a necessity of more accurate investigations in all steps of this process. In this study, the effects of sperm dilution ratio on post-thaw sperm quality of Prochilodus lineatus were evaluated. Sperm was diluted in a standard freezing medium (glucose and methyl glycol) at four different ratios (sperm to final volume = 1:5, 1:10, 1:50 or 1:100), frozen in a nitrogen vapour vessel at –170°C and then stored in liquid nitrogen vessel at –196°C. Post-thaw motility rate and velocities (curvilinear = VCL; average path = VAP; straight line = VSL) were determined using a Computer-Assisted Sperm Analyzer (CASA) at 10 and 40 s post-activation. The highest motility rates were observed when sperm was frozen at a ratio of 1:5 (76%) and 1:10 (75%). The highest VCL (225 μm/s) and VAP (203 μm/s) were observed at a ratio of 1:10, while VSL was similar among samples frozen at 1:5, 1:10 and 1:50 (97–124 μm/s). When those parameters were evaluated again 30 s later, motility decreased significantly in samples frozen at a ratio of 1:5 (57%) and 1:10 (61%), while velocities decreased significantly in all samples regardless of dilution ratio (75–85 μm/s of VCL, 38–53 μm/s of VAP and 25–39 μm/s of VSL). P. lineatus sperm should be frozen at a ratio of 1:10, where both the number of loaded sperm per straw and the post-thaw quality are maximized.